(untitled) (Papeles, 2026)
Introduction: This article compiles some promising curricular practices that promote human rights education and education for sustainable development in the teacher training institutions of the City of Buenos Aires (Argentina). Methodology: To this end, I analyzed the curriculum of the degree to become a teacher at the primary level and the curricula of the degrees that allow to teach the following subjects at the secondary level: Biology, Political Science, Economics, Geography, Chemistry, Physics, Education Sciences, Computer Science, Management and Business Administration, History, Philosophy, Psychology, Language and Literature, Technology, and Mathematics. The paper also includes, at the beginning, an explanation on how teacher training works in the City of Buenos Aires and the announcement of the thematic focus. Results and discussions: The article continues with the documentary analysis itself, with textual references related to human rights and/or sustainable development found in the curricula. Each of the degrees has curriculum requirements that promote these agendas, including a mandatory course on Integral Sexual Education. Conclusions: Although in most cases there is no compulsory subject specifically on human rights or sustainable development, and recognizing that in many cases the references to these issues are present in optional courses, it remains true that the curricula are permeated by these agendas. Among the main topics mentioned are gender, diversity, equality and inclusion, and democracy, citizenship, and the functioning of the State. In contrast, for example, there is not much work on the Convention on the Rights of the Child. The compilation and dissemination of good curricular practices in human rights education should serve to promote this agenda, inspire the Latin American region to adopt similar proposals, and foster continued cooperation and collaboration to generate synergies.